Peran Ulama Dan Negara Dalam Regulasi Merokok Menurut Syariat Islam - Faisal Mys, Muhammad; Syahputra, Akmaluddin; Syahmedi Siregar, Ramadhan (Kamaya: Jurnal Ilmu Agama, 2025)
This study aims to analyze the role of religious scholars and the state in regulating cigarette consumption in Indonesia based on the perspective of Islamic law. This study uses a normative legal method with a literature review approach. Although the negative effects of cigarettes on health and the environment have been scientifically proven, regulations in Indonesia remain permissive and rely solely on control measures rather than prohibition. From a religious perspective, fatwas issued by religious scholars, such as those from the Indonesian Ulema Council (MUI), state that smoking, especially in public places, for children and pregnant women is haram (forbidden). However, these fatwas have not been consistently followed, either by religious leaders themselves or by the general public. From the state's perspective, regulations through Law No. 36 of 2009 and Government Regulation No. 109 of 2012 tend to only restrict the distribution and promotion of cigarettes without directly addressing individual consumption. The main focus of the analysis lies in the lack of harmony between the fatwa of religious scholars, which generally prohibits smoking, especially for vulnerable groups and in public spaces, and state policies that tend to be permissive and only serve as a form of control. The results of the study indicate a lack of harmony between religious norms and state law, as well as the need for integration between fatwas issued by religious scholars and state policies in order to create an effective regulatory system that prioritizes the welfare of the people. This study contributes to strengthening public health regulations based on maqashid syariah, particularly in efforts to protect life (hifz al-nafs) and achieve the welfare of the people through synergy between religious norms and state law.